Understanding the Antecedents of Green Cosmetics Purchase Among Indonesian Consumers - Annisa Mutiara; Melia Famiola; Ida Ayu Saras Valendia; Jasmine Raihana (Profesional Muda Cendekia Publishing, 2023)
Green cosmetics have an added value where they are not only made of natural ingredients, but also being produced with less pollution, free from animal cruelty and using less of non-renewable materials. Previous research shows that environmental concerns tend to have a significant effect on the purchase intention of the green cosmetics. Yet, consumers react differently toward the idea of green cosmetics itself, it becomes important to have solid understanding on the internal and external factors that lead to a purchase decision. This research aims to understand Indonesian consumers’ behavior toward green cosmetics by adapting the theory of reasoned action (TRA) framework. It focuses on how consumers’ attitude toward green cosmetics and subjective norms could affect the purchase intention, which would later affect the purchase decision. This research conducted using the survey method. The questionnaire consists of 5 Likert scales. The data analysis of this research was conducted by using the latent variable analysis (lavaan) packages on RStudio. From the test results, it was found that attitude and subjective norm positively affect purchase intention. Then, purchase intention and environmental responsibility have a positive effect on the purchase decision of green products. This study contributes to the literature of green marketing, and future research is expected to reach more green cosmetic users to be more representative.